The Medical Works of Moses Maimonides: New English Translations based on the Critical Editions of the Arabic Manuscripts - Bos, Gerrit (Brill, 2021)
This edition contains the collected English translations of the series The Medical Works of Moses Maimonides (17 vols., 2002-2021) that were published by Gerrit Bos in parallel critical editions along with the original Arabic texts. The collection offers three main medical treatises by Maimonides (1138-1204) ( Medical Aphorisms ; Commentary on Hippocrates' Aphorisms ; On Poisons and the Protection against Lethal Drugs and six minor ones ( On Coitus ; On the Regimen of Health ; On the Elucidation of Some Symptoms and the Response to Them ; On Hemorrhoids ; On Asthma ; On Rules Regarding the Practical Part of the Medical Art , presented for the first time in one harmonized volume, supplemented by indexes of diseases, medicinal ingredients, and quoted physicians.